Configuration of the Earth's Magnetotail Current Sheet. Issue 6 (24th March 2021) - Artemyev, Anton; Lu, San; El‐Alaoui, Mostafa; Lin, Yu; Angelopoulos, Vassilis; Zhang, Xiao‐Jia; Runov, Andrei; Vasko, Ivan; Zelenyi, Lev; Russell, Christopher
Abstract: The spatial scale and intensity of Earth's magnetotail current sheet determine the magnetotail configuration, which is critical to one of the most energetically powerful phenomena in the Earth's magnetosphere, substorms. In the absence of statistical information about plasma currents, theories of the magnetotail current sheets were mostly based on the isotropic stress balance. Such models suggest that thin current sheets cannot be long and should have strong plasma pressure gradients along the magnetotail. Using Magnetospheric Multiscale and THEMIS observations and global simulations, we explore realistic configuration of the magnetotail current sheet. We find that the magnetotail current sheet is thinner than expected from theories that assume isotropic stress balance. Observed plasma pressure gradients in thin current sheets are insufficiently strong (i.e., current sheets are too long) to balance the magnetic field line tension force. Therefore, pressure anisotropy is essential in the configuration of thin current sheets where instability precedes substorm onset. Plain Language Summary: Interaction between solar wind plasma flows and Earth's magnetic field forms the magnetotail, an elongated plasma region in the nightside magnetosphere with strong equatorial sheet‐like plasma currents. That current sheet's spatial scales and intensity determine the magnetotail configuration, which is critical to one of the most energetically powerful phenomena in the Earth's magnetosphere, substorms. In the absence of statistical information about plasma currents, theories based on the isotropic stress balance imply current sheets that are insufficiently intense and thin to trigger substorms. Using MMS and THEMIS observations and global simulations, we explore magnetotail current sheet configuration. We find that the magnetotail current sheet is thinner than expected from theories that rely on isotropic stress balance. Therefore, pressure anisotropy is essential to the prolonged thin current sheet stability that precedes substorm onset, and thus it must be included in space weather models. Key Points: We conduct statistics on current densities in the magnetotail current sheet using Magnetospheric Multiscale and THEMIS observations The most intense and thinnest current sheets cannot be described by isotropic pressure balance Comparison of statistical observations with global magnetohydrodynamic and hybrid simulations confirm main findings